Percutaneous Interventions for Injuries in Athletes: Implications on Return to Play - Varela-Margolles, Diana; Milani, Ava; Kamel, Sarah I. (Seminars in Musculoskeletal Radiology, 2024)
For nonsurgical musculoskeletal (MSK) injuries in athletes, image-guided percutaneous intervention may aid in recovery and decrease return to play (RTP) time. These interventions fall into two major categories: to reduce inflammation (and therefore alleviate pain) or to promote healing. This review describes the risks and benefits of the various percutaneous interventions in MSK athletic injury and surveys the literature regarding the implication of these interventions on RTP.
Keywords: platelet-rich plasma; percutaneous tenotomy; dry needling; corticosteroid injection; tendinopathy